Phonological and cognitive correlates of word-reading acquisition under two different instructional approaches in Greek - Papadopoulos, Timothy C. (European journal of psychology of education, 2001)
This study examined whether phonological and cognitive tasks correlate with beginning reading acquisition in Hellenic populations under two different instructional approaches: a whole language approach supplemented by implicit coding instruction through incidental learning, as used in Cyprus, versus the syllable-splitting approach characterised by explicit decoding instruction, as used in Greece. Planning, attention, simultaneous, and successive processing tasks together with three phonological coding tasks (Oddity task, Phoneme Elision, and Sound Isolation) were administered to 50 Greek and 50 Cypriot Grade 1 students. Word Attack and Word Identification were also administered to measure early reading competency. The main findings of the study were as follows: (a) significant group differences were revealed in word-decoding accuracy but not in real-word reading accuracy, an expected finding in a system characterised by high grapheme-phoneme consistency; (b) successive processing and phonological coding consisted of the fundamental abilities that differentiated the Greek from the Cypriot first-graders; and (c) the Greek group exhibited a higher linguistic ability than the Cypriot group. This was facilitated by the use of the distal cognitive processes to reading, that is, successive and simultaneous processing. The discussion focuses on the need to reconsider the nature of early reading instruction in languages such as Greek with high grapheme-phoneme consistency. Cette enquête examine phonologiquement et cognitivement les méthodes nécessaires pour le début de l'acquisition de la lecture dans la population Hellénique, en deux différents types d'instruction: toute la langue d'un approche supplémentaire, sous-entendu, d'une instruction codée d'un enseignement symptomatique, comme il est utilisé en Chypre, contre l'approche division de la syllabe, caractérise de l'instruction explicite du décodage, utilisé en Grèce. Le plan, l'attention, la simultanéité, les méthodes successives du processus, avec les trois taches phonologiques (la tâche de la singularité, l'élision du phonème et l'isolation du son) étaient donnes aux 50 étudiants Grecs, et 50 étudiants Chypriotes de premier degré. L'attaque du mot et son identification étaient aussi utilisées pour tester la première compétence de la lecture. Les résultats de l'enquête étaient: (a) des différences significatives étaient révèles à la précision du décodage du mot, mais ce n'était pas le cas à la précision de la lecture du vrai-mot, un résultat normal dans un système caractérisé d'une haute consistance du graphème-phonème; (b) un progrès successif et décodage phonologique qui différencient les étudiants du premier degré entre la Grèce et le Chypre et (c) le groupe grec a démontré une habileté linguistique plus élevée que le groupe chypriote. C'était facilite de l'usage d'un processus cognitif double, qui est un processus successif et simultané. La discussion est centralisée sur la nécessité de reconsidérer la nature de la première instruction de la lecture, quand aux langues comme le Grec avec une haute consistance du graphème-phonème.